Comparative analysis of advanced technologies for authenticating users by keystroke dynamics - Алексеев, В.А.; Маслий, Д.В.; Горелов, Д.Ю. (Radiotekhnika, 2017)
A comparative analysis of research results in the direction of authenticating users by keystroke dynamics over the past few decades with using common probabilistic statistical models and machine learning algorithms is given. The main criteria for the effectiveness of authentication systems based on the analysis of the keystroke dynamics features are formulated.